Avoiding inappropriate paediatric admission: facilitating General Practitioner referral to Community Children’s Nursing Teams - Kyle Richard G; Banks Michele; Kirk Susan; Powell Peter; Callery Peter (BMC Family Practice, 2013)
Abstract Background Children’s emergency admissions in England are increasing. Community Children’s Nursing Teams (CCNTs) have developed services to manage acutely ill children at home to reduce demand for unscheduled care. Referral between General Practitioners (GPs) and CCNTs may reduce avoidable admissions and minimise the psychosocial and financial impact of hospitalisation on children, families and the NHS. However, facilitators of GP referral to CCNTs are not known. The aim of this study was to identify facilitators of GP referral to CCNTs. Methods Semi-structured interviews with 39 health professionals were conducted between June 2009 and February 2010 in three Primary Care Trusts served by CCNTs in North West England. Interviewees included GPs, Community Children’s Nurses (CCNs), consultant paediatricians, commissioners, and service managers. Qualitative data were analysed thematically using the Framework approach in NVivo 8. Results Five facilitators were identified: 1) CCN/CCNT visibility; 2) clear clinical governance procedures; 3) financial and organisational investment in the role of CCNTs in acute care pathways; 4) access and out of hours availability; 5) facilitative financial frameworks. Conclusion GPs required confidence in CCNs’ competence to safely manage acutely ill children at home and secure rapid referral if a child’s condition deteriorated. Incremental approaches to developing GP referral to CCNTs underpinned by clear clinical governance protocols are likely to be most effective in building GP confidence and avoiding inappropriate admission.